Recipe costing : the bottom line. - 4 0 16; Culinary Institute of America; 5 Culinary Institute of America (New York, 2007)
Food costs and menu pricing can make or break your restaurant or foodservice business. The CIA's Recipe Costing DVD will help you uncover the secrets of controlling food costs and help your operation realize higher revenues. Controlling food costs is essential when managing a foodservice operation. When you implement Recipe Costing into your staff's culinary training, they will: learn the importance of standard recipes and portion sizes ; watch a yield test being conducted on individual ingredients to determine a total recipe cost ; study the principles of units of measure, weight vs. volume, cost per unit, and edible portion quantity.
DVD format.
Keywords: 2 -- 0; 6; Menus.;Food service. -- 20; 20; 2